Pengaruh LDR, BOPO, NPL dan Mobile Banking terhadap Profitabilitas - Pasaribu, Magdhalena Br; Riyadi, Selamet (Universitas muhammadiyah palembang, 2022)
This study aims to analyze the effect of the Loan to Deposit Ratio (LDR), Operating Costs of Operating Income (BOPO), Non Performing Loans (NPL), and Mobile Banking (MB) on Profitability (ROA) at PT Bank Tabungan Negara (Persero) Tbk from 2011 to 2020. The multiple Linear Regression Analysis Model is used to determine the magnitude of the relationship between the independent variable and the dependent variable while testing the hypothesis by using a t-test (partial) and f-test (simultaneous). Based on the results of the study from 2011 to 2020, it was concluded that the t-test (partial) showed that LDR had an insignificant positive effect on profitability. BOPO has a negative and significant effect on profitability. NPL and MB show that the two independent variables have no significant negative effect on profitability. With the f test (simultaneous) the significance of the effect of the independent variables, LDR, BOPO, NPL, and MB on the dependent variable Profitability can be concluded simultaneously has a significant positive effect on Profitability. The coefficient of determination adj R2 is 97.1%, this indicates that there is a very strong correlation where the independent variables LDR, BOPO, NPL, and MB greatly affect profitability, while 2.9% of other variables are outside the model of this study.